2003
DOI: 10.1306/041703730941
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Sedimentation and Subsidence History of Lake Baikal, Siberia, Based on Seismic Stratigraphy and Coring

Abstract: The long, continuous, high-latitude, stratigraphic record of Lake Baikal was deposited in three broad sedimentary environments, defined by high-resolution seismic-reflection and coring methods: (1) turbidite depositional systems, by far the most widespread, characterizing most of the margins and floors of the main basins of the lake, (2) large deltas of major drainages, and (3) tectonically or topographically isolated ridges and banks. Holocene sedimentation rates based on radiocarbon ages vary by more than an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 44 publications
2
35
0
1
Order By: Relevance
“…These two estimates suggest 100 m of sediment would require between ∼125 and 50 ka, much longer than the 40 ka constraint placed by the C 14 ages. The 0.8-2 mm/year sedimentation rates are consistent with long-term sedimentation rates in lakes in volcanically and tectonically active areas such as Lake Chalpas, Guatemala, and Lake Baikal in Siberia (Edgington et al, 1991;Fernex et al, 2001;Colman et al, 2003), with 2 mm/year being at the extreme. Thus, these are reasonable sedimentation rates, but they require more than 40 ka to build the ∼100 m sequence of sediments on Samosir.…”
Section: Modeling Resurgence At Tobasupporting
confidence: 70%
See 1 more Smart Citation
“…These two estimates suggest 100 m of sediment would require between ∼125 and 50 ka, much longer than the 40 ka constraint placed by the C 14 ages. The 0.8-2 mm/year sedimentation rates are consistent with long-term sedimentation rates in lakes in volcanically and tectonically active areas such as Lake Chalpas, Guatemala, and Lake Baikal in Siberia (Edgington et al, 1991;Fernex et al, 2001;Colman et al, 2003), with 2 mm/year being at the extreme. Thus, these are reasonable sedimentation rates, but they require more than 40 ka to build the ∼100 m sequence of sediments on Samosir.…”
Section: Modeling Resurgence At Tobasupporting
confidence: 70%
“…If the 74-33.7 ka rate was also 4.9 cm/year then the 500-400 m of uplift discussed above would have been achieved in ∼10-8 ka respectively, requiring sedimentation rates as high as 1-1.25 cm/year or 10-12.5 mm/year to produce the 100 m of sediment on Samosir before it emerged. Such rates are up to two orders of magnitude higher than sedimentation rates in the aforementioned lakes (Edgington et al, 1991;Fernex et al, 2001;Colman et al, 2003). We therefore consider uplift at the 33.7-22.5 ka rate of 4.9 cm/year untenable for the 74-33.7 ka period as it would require unrealistic sedimentation rates for Lake Toba.…”
Section: Modeling Resurgence At Tobamentioning
confidence: 99%
“…The published interpretations about its lake-level fluctuations ranged between two contradicting estimations. Romashkin and Williams (1997) mentioned an extremely huge range of climatically induced lake-level fluctuations of about 450 m. Colman (1998) and Colman et al (2003), on the other hand, refused the possibility of considerable climatically induced lake-level changes for Lake Baikal. The authors pointed out that the observed relative lakelevel changes were mainly caused by tectonic activity.…”
Section: Comparison With Other Records From Lake El'gygytgynmentioning
confidence: 99%
“…Turbidites represent deposits of turbulent, high-energy conditions, triggered by catastrophic events: breakdowns of delta slopes, voluminous mud flows and excessive floods in the catchment (Sturm and Matter, 1978;Girardclos et al, 2007). Alterations of pelagic mud and turbidites indicate that normally calm sedimentation conditions within the deep basins of Lake Baikal are interrupted occasionally by high-energy turbidity currents and by rapid re-deposition of older material from far distance sources (Nelson et al, 1999;Colman et al, 2003;Vologina et al, 2003). Analogical, we suggest distant sources for the turbidites of the deep-water cores BAIK00-1 and BAIK08-2 (Fig.…”
Section: Mineralsmentioning
confidence: 99%
“…It has been shown that biological, physical and geochemical processes all influence biological and geochemical variability in the lake Flower, 1998;Müller et al, 2005;Granina and Callender, 2007;Schmid et al, 2008). Detailed studies of the lake bottom morphology and of composition and age of sediments in the different basins have been used, to further our understanding of processes of sediment formation and accumulation in Lake Baikal (Potrik'eva, 1959;Karabanov et al, 1984;Appleby et al, 1998;De Batist et al, 2002;Colman et al, 2003;Vologina and Sturm, 2009) and to studying past environmental and climate changes (Kuzmin et al, 2000;Bangs et al, 2000;Grachev et al, 2002;Fietz et al, 2005;Mackay, 2007). Formation and deposition of turbidities within the deep basins of Lake Baikal have been investigated and described within the conceptual principles of turbidity current formation in freshwater basins (Sturm and Matter, 1978).…”
Section: Introductionmentioning
confidence: 99%